2018
DOI: 10.1038/s41477-018-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of the productivity potential of CAM

Abstract: There is considerable interest in transferring crassulacean acid metabolism (CAM) to C crops to improve their water-use efficiency. However, because the CAM biochemical cycle is energetically costly, it is unclear what impact this would have on yield. Using diel flux balance analysis of the CAM and C leaf metabolic networks, we show that energy consumption is three-fold higher in CAM at night. However, this additional cost of CAM can be entirely offset by the carbon-concentrating effect of malate decarboxylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
143
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(154 citation statements)
references
References 43 publications
10
143
0
1
Order By: Relevance
“…A bottom-up approach builds on existing mechanistic models (Owen and Griffiths, 2013a;Hartzell et al, 2018) and metabolic network models (Maurice Cheung et al, 2014;Shameer et al, 2018). Such models posit a null state, in which the only a minimal circadian and/or metabolic regulation is imposed on selective model components.…”
Section: Computational Approaches Needed To Define Metabolic and Envimentioning
confidence: 99%
“…A bottom-up approach builds on existing mechanistic models (Owen and Griffiths, 2013a;Hartzell et al, 2018) and metabolic network models (Maurice Cheung et al, 2014;Shameer et al, 2018). Such models posit a null state, in which the only a minimal circadian and/or metabolic regulation is imposed on selective model components.…”
Section: Computational Approaches Needed To Define Metabolic and Envimentioning
confidence: 99%
“…However, as a 42 carbon-concentrating mechanism, CAM is thought to be more metabolically expensive than C 3 43 (Winter and Smith, 1996b), which suggests that transferring a CAM pathway into C 3 crops 44 would incur a crop yield penalty. To investigate the energetics of C 3 and CAM, large-scale 45 metabolic models were applied which showed that engineering CAM into C 3 plants does not 46 impose a significant energetic penalty given the reduction in photorespiration from the carbon-47 concentrating mechanism (Cheung et al, 2014;Shameer et al, 2018). 48…”
mentioning
confidence: 99%
“…Firstly, a reaction for the accumulation of oxygen, which is produced from 72 water splitting in the photosynthetic light reactions, was added to the model such that we could 73 run the simulations for CAM and CAM idling as oxygen exchange was constrained to zero 74 during the day in these two scenarios. Another modification from Shameer et al (2018) was how 75 the acidification of the vacuole was modelled. Instead of directly setting different fixed pH for 76 the vacuole in C 3 and CAM, protons were allowed to accumulate in the vacuole in our model.…”
mentioning
confidence: 99%
See 2 more Smart Citations